Evaluating the Impact of Sustainability and Pipeline Quality on Global Crude Oil Supply Chain Efficiency - Jain, Sunny Paraskumar; Jones, Erick; Gupta, Shalini; Okate, Samuel I (International Journal of Supply Chain Management, 2014)
In this paper, the efficiency Curve model shown in Modelling the Supply Chain (Author: Shapiro) is modified to compare Crude oil supply chain among Indonesia, Russia and Columbiabased on oil transportation distances and associated cost, refinery costs, and the costs associated with refinery sustainability and pipeline quality. However this model was originally used to determine the optimal locations of distribution centres based on transportation cost and the capacity of the distribution centres, this model was modified to allow the use of different costs associated with the quality condition of the pipeline and the costs of sustaining an environmentally friendly facility. This case used to optimize the total cost of oil supply chain for Indonesia, Russia and Columbia. We seek to extend our previous supply chain model, which represent the outbound oil supply chain. The outputs of this paper are efficiency curve that show how the costs of pipeline quality and facility sustainability affect the overall costs of the oil industry of Indonesia, Russia and Columbia. Keywords supply chain management, efficiency curve, quality, sustainability, optimization, crude oil supply chain, Russian Oil pipeline, and Oil refinery.